Perceptions and challenges of technological use in teaching among late-career teachers: a case study in Cambodia - Sonita Pen; Patricia D. Morrell (Springer, 2024)
Abstract The COVID-19 pandemic created a huge demand in using Information and Communication Technology (ICT) in teaching and learning. Teachers are believed to be a main influencer in a student's learning, so it is important to have a deep insight of teachers' perceptions of ICT integration in teaching and the problems they have been facing in ICT integration. However, little has been known about these aspects, especially regarding late-career teachers in Cambodia. This study investigated late-career teachers' perceptions and barriers to incorporating technology into teaching practices at an urban high school to shed light on possible solutions and appropriate methods to encourage the use of ICT in teaching. Six late-career teachers teaching various subjects at a public high school located in the capital city of Cambodia served as the interview sample. The outcome indicates that the general view and sentiment of late-career teachers toward the use of ICT were positive. Late-career teachers' use of ICT in teaching were found to be hindered by first-order, second-order, and third-order barriers. Recognizing the limited sample, suggestions to encourage ICT use are offered.